Prognostic value of final pathological stage in colon adenocarcinoma after neoadjuvant chemotherapy: A propensity score-matched study - Xiang, Meijuan; Liang, Zongyu; Gao, Yuan; Feng, Xingyu; Yao, Xueqing (Frontiers in Surgery, 2022)
Background: Neoadjuvant chemotherapy (NAC) could improve local tumor control of locally advanced colon cancer (LACC), but the prognostic value of yp stage in colon cancer remains unknown. Here, we aimed to ascertain yp stage as an indicator for LACC prognosis after NAC. Methods: The data of patients diagnosed with colon adenocarcinoma between 2004 and 2015 were extracted from the Surveillance, Epidemiology, and End Results database. After 1:2 propensity score matching, cancer-specific survival (CSS) and overall survival (OS) were compared between the NAC and Non-NAC groups of different stage classifications. The correlation between clinical and pathological factors and CSS was identified. Results: A total of 49, 149, and 81 matched pairs of stage 0–I, II, and III patients, respectively, were generated for analysis. For stage 0–I (p = 0.011) and III (p = 0.015), only CSS in the NAC groups were inferior. There was no significant difference in CSS of stage II (p = 0.89) or OS of all stages between the NAC and Non-NAC groups (p = 0.87 for stage 0–I, p = 0.074 for stage II, and p = 0.13 for stage III separately). Receiving NAC was an independent prognostic risk factor for patients with stage 0–I (hazard ratio, 4.377; 95% confidence interval, 1.276-15.013; p = 0.019) and stage III (hazard ratio, 1.657; 95% confidence interval, 1.069-2.567; p = 0.024). Conclusions: The CSS was poorer among LACC patients who underwent NAC than among those who did not. The yp stage of colon cancer after NAC has distinctive significance, which may contribute to predicting the prognosis and guiding the treatment of LACC patients after NAC.